Tuberculosis treatment outcomes and the predictors for survival of tb/hiv co-infected patients in the Klang Valley, Malaysia / Ismawati Binti Ismail - Ismail, Ismawati (2014)

(untitled)
Background: Tuberculosis and human immunodeficiency virus (TB/HIV) co-infection are important global public health problems. Tuberculosis (TB) is the most common opportunistic infection and the leading cause of death in HIV-infected patients. Co-infection with TB and HIV is a situation that is becoming rampant worldwide and Malaysia is no exception. However, there are no substantial data concerning the co-infection of both diseases in this country. Objectives: To determine the risk factors for defaulters of TB treatment and predictors of death among TB/HIV co-infected patients in Malaysia. Methods: Medical records at the time of TB diagnosis and subsequent follow-up of all newly registered TB patients with HIV co-infection seen at TB clinics in the Institute of Respiratory Medicine and three public hospitals in the Klang Valley between January 2010 and September 2010 were reviewed. These medical records were reviewed again twelve months after their initial diagnosis to determine TB treatment outcomes and survival. Kaplan Meier and Cox proportional hazard regression analysis were performed using SPSS. Results: Of 227 patients analysed, the majority of patients were males (88.1%) and single/divorced (67.0%). A total of 48.5% were Malays. The mean age of the patients was 39.1 (standard deviation 8.6). The most common mode of HIV transmission was through injecting drug use (55.9%). Among 227 patients, successful outcomes were achieved in 117 patients (53.4%) with 18.7% of patients ‘cured’ and another 34.7% ‘completed treatment’. The unsuccessful outcomes were those who ‘defaulted treatment’ (25.6%, n=56), ‘died’ iv (21.0%, n=46); and another 8 (3.4%) who were still on treatment. There were no cases of treatment failure. After adjusting for other predictors in multiple Cox regression analysis, the significant predictors of default from TB treatment in HIV-infected patients were: (i) not on antiretroviral therapy (AHR 3.75; 95%CI 2.19-6.42), (ii) low serum albumin level (AHR 2.89; 95%CI 1.22-6.84), (iii) presence of lymphadenopathy (AHR 2.03; 95%CI 1.18-3.49) and (iv) alcohol intake (AHR 1.93; 95%CI 1.10-3.38). At the end of the study, seven (7) patients who were originally classified as defaulters were later reclassified as having died, making the total number of deaths during TB treatment 53 (23.3%), with 40% of deaths occurring within two months of TB diagnosis. Survival at 2, 6 and 12 months after initiating TB treatment were 90.7%, 82.8% and 78.8% respectively. After adjusting for other factors, death in TB/HIV co-infected patients were associated with being Malay (AHR 4.48; 95%CI 1.73-11.64), CD4 T-lymphocytes count < 200 cells/μl (AHR 3.89; 95% CI 1.20-12.63), three or more opportunistic infections (AHR 3.61; 95% CI 1.04-12.55), not receiving antiretroviral therapy (AHR 3.21; 95% CI 1.76-5.85) and increase per 103 total white blood cell count per microliter (AHR 1.12; 95% CI 1.05-1.20). Conclusion: TB/HIV co-infected patients had a high case fatality rate during TB treatment. Initiation of antiretroviral therapy in these patients can improve survival by restoring immune function and preventing opportunistic infections.